A precisely positioned chiral center in an i, i + 7 tether modulates the helicity of the backbone peptide. Issue 50 (6th June 2017) - Hu, Kuan; Sun, Chengjie; Yang, Dan; Wu, Yujie; Shi, Chuan; Chen, Longjian; Liao, Tao; Guo, Jialin; Liu, Yinghuan; Li, Zigang
Abstract : A chiral center of R absolute configuration at the γ-position to the C-terminal of a 10-membered tether could function to efficiently induce helicity of the backbone peptides. Abstract : In some cases, helical peptides stabilized by an i, i + 7 tether exhibit better target binding and cellular functions compared to their i, i + 4 analogues. Herein, we carried out a systematic study of the effects of an in-tether chiral center on the i, i + 7 system. We screened the optimal cross linking mode, tether length, in-tether chiral center positions, and absolute configurations. From these studies, we determined that a chiral center of R absolute configuration at the γ-position to the C-terminal of a 10-membered tether could function to efficiently induce helicity of the backbone peptides. This is an important addition to the current i, i + 4 in-tether chiral center induced helicity strategy (CIH strategy), and could have broad biological applications.